Adaptive Output Tracking Control of a Surface Vessel - Lee, Dongbin; Tatlıcıoğlu, Enver; Tatlıcıoğlu, Enver; Burg, Timothy C.; Dawson, Darren M. (Institute of Electrical and Electronics Engineers Inc., 2008)
In this paper, the tracking control of a three degree-of-freedom marine vessel is examined. The novelty of this work is the transformation of the asymmetric inertia matrix into a symmetric, positive definite matrix. The asymmetry arises from the added mass common to practical surface vessels and creates a significant challenge for control design. The control design is further complicated by the parametric uncertainties in the dynamic model of the vessel. Two adaptive control schemes with a projection-based adaptation law are proposed: a full-state feedback controller and an output feedback controller. Both controllers are known to yield a uniformly ultimately bounded tracking result in the presence of parametric uncertainty. Numerical simulation results are shown to demonstrate the validity of the proposed controllers.
47th IEEE Conference on Decision and Control, CDC 2008; Cancun; Mexico; 9 December 2008 through 11 December 2008
Keywords: Feedback control; Adaptation laws; Control designs; Inertia matrixes; Output feedback controllers; Surface vessels